THE ROLE OF MIRANSHOH SULTAN IN THE STABILITY OF THE TEMURID’S STATE - Begimqulova L. M. (TARIXIY TADQIQOTLAR, 2025)
This article analyzes the youth, political and military activities of Amir Timur’s third son, Miron Shah Sultan, as well as his role in the stability and expansion of the Timurid empire. Based on historical sources, including the works of authors such as Sharafiddin Ali Yazdi, Ibn Arab Shah and Klavix, the positive and negative aspects of Miron Shah’s personality and activities are highlighted. The article also examines the mental state of Miron Shah Sultan, his achievements and shortcomings in governance based on an objective approach.